Other wind - Le Guin, Ursula K. (New York Ace Books, 2003)
The sorcerer Alder has the power of mending, but it may have become the power of destruction: every night he dreams of the wall between the land of the living and the land of the dead, and the wall is being dismantled. If the wall is breached, the dead will invade Earthsea. Ged, once Archmage of Earthsea, sends Alder to King Lebannen. Now Alder and the king must join with a burned woman, a wizard of forbidden lore, and a being who is woman and dragon both, in an impossible quest to save Earthsea.
Mending the green pitcher -- Palaces -- Dragon council -- Dolphin -- Rejoining.
Originally published: [New York] : Harcourt, 2001.
96643
Keywords: Imaginary places; Wizards; Fantasy fiction